Verifying documentation form for Greater Scaup sighting submitted by Thomas H. Kent, December 20 1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1980)
A form submitted by Thomas Kent documenting the sighting of a Greater Scaup on December 20, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed